Handling Radar Cross-Section Performance in Monitoring Vital Signs Under Constraint Conditions - Khan, Faheem; Sherazi, Saleh M.; Khan, Naeem; Ashraf , Imran; Khan, Fahad (Frontiers in Signal Processing, 2021)
Two vital signs including heartbeat and respiratory rate are monitored in this work under two constraint situations; namely noise disturbance and intermittent observations. The existing scheme for finding, measuring and monitoring vital signs was Fourier Transform which could not deal with non-stationary process. As an alternative, the Wavelet Transforms are used in this work which is equally applicable to both stationary and non-stationary processes. In addition, the loss of output data may result in crucial implications in observing vital signs. Formerly, only un-interrupted data has been amalgamated in tracing vital signs. A novel adaptive ARMA-based scheme is proposed to obtain optimum estimated results in the presence of the above two critical scenarios. Simulation results obtained on real (practical) data show that the ARMA-based model produces similar vital signs as shown by clean and un-distorted data.